Strategi Guru Dalam Mengatasi Kesulitan Anak SD Membaca Al-Quran Pada Anak Berkebutuhan Khusus (Autis) Disekolah Alam Almahira Kota Bengkulu - Fidhia Andani; Ranti Marta Lina; Thias Cahya Lestari; Mela Anteza; Nani Agustin (Yayasan Darussalam Bengkulu, 2023)
The purpose of this study is to determine and analyze teacher strategies in overcoming the difficulties of elementary school children reading the Quran in children with special needs (autism) at Almahira Nature School, Bengkulu City. Autistic children are unable to interact socially, even as if living in their own world. This is what autistic children experience at Almahira Nature School, Bengkulu City, but as teachers, strategies are needed to overcome difficulties in reading the Quran in autism. This study emphasizes the ways and strategies of teachers guiding reading the Quran using qualitative methods, which are descriptive. Data collection techniques used are observation and interviews. The results of this study found that the methods used through a psychological approach to children, creating a conducive class and guiding them individually. The strategies used are designing direct learning, using the Iqra method, using learning media and evaluation.